PEMBERDAYAAN MASYARAKAT MELALUI INOVASI TEKNOLOGI DAN SOP PENGELOLAAN WISATA PANDANSILI, DESA NGAMPUNGAN, BARENG, JOMBANG - Ali, Machrus; Jatmiko, Anang; Muzajjad, Ach.; Dwiningwarni, Sayekti Suindyah (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2023)
The tourism industry has created a new environment in the world of tourism called Smart Tourism. Smart Tourism is one of the pillars of Smart City. Smart Tourism is one of the pillars of Smart City. Smart Tourism is defined as an ICT tourism platform integrated with the role of information technology and efficient services for tourists. So innovation technology, business management, and Pokdarwis Standard Operating Procedures (SOP) are needed. The approach method with partners is using the Asset Based Communities Development (ABCD) method. This approach focuses on inventorying assets in the community which are assumed to be very supportive of community empowerment activities. Increasing Community Empowerment Through Smart Tourism and Strengthening Management in Pandansili Tourism. Providing training on solar panel installation, training on using the Internet of things, business management training, and creating Standard Operating Procedures (SOP). From the results of training and mentoring, this program succeeded in increasing partner turnover, from 16 million – 30 million rupiah to 42 million – 42 million rupiah per month. The training and assistance with solar panel installation were very beneficial for the participants, this was shown by the participants' enthusiasm for taking part in the training and also the results of structured interviews conducted by the Team after the participants took part in the training which showed an increase in knowledge and understanding from 17% to 73.5%. Internet of Things training and assistance was highly requested by participants, this was shown by the enthusiasm of participants to immediately practice using their respective Androids in the classroom and participants asked questions directly to the resource persons. there was an increase in knowledge from 14.5% to 64.5%. Increased knowledge, understanding, and skills of participants regarding designing Pokdarwis management SOPs from 33.5% to 74.5%. This assistance will continue through innovation and other training